2015
DOI: 10.2174/1874467208666150507110359
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Unified Theory of Calmodulin Regulation (Calmodulation) of Voltage-Gated Calcium and Sodium Channels

Abstract: Voltage-gated Na and Ca2+ channels represent two major ion channel families that enable myriad biological functions including the generation of action potentials and the coupling of electrical and chemical signaling in cells. Calmodulin regulation (calmodulation) of these ion channels comprises a vital feedback mechanism with distinct physiological implications. Though long-sought, a shared understanding of the channel families remained elusive for two decades as the functional manifestations and the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 202 publications
(434 reference statements)
0
59
0
Order By: Relevance
“…[15, 16, 22, 33, 41] These studies of Na V -CaM interactions contrast with the behavior of IQ motifs in voltage-dependent calcium channels such as Ca V 1.2, which interacts with both domains of CaM and has a higher affinity for (Ca 2+ ) 4 -CaM than apo CaM [8991], despite the similarities between the calcium and sodium channels. [92]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15, 16, 22, 33, 41] These studies of Na V -CaM interactions contrast with the behavior of IQ motifs in voltage-dependent calcium channels such as Ca V 1.2, which interacts with both domains of CaM and has a higher affinity for (Ca 2+ ) 4 -CaM than apo CaM [8991], despite the similarities between the calcium and sodium channels. [92]…”
Section: Discussionmentioning
confidence: 99%
“…[92, 116119] For many of these channels, CaM is associated under resting (low calcium) conditions as it is with Na V 1.2. CaM may activate, inhibit, or do both, depending on its fractional saturation by calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium entry through CNGCs evolved self‐inactivation machinery to prevent Ca 2+ overload and shape calcium signals. The classical Ca 2+ ‐dependent inactivation (CDI) of animal CNGCs, which includes interaction between CNGC‐embedded calmodulin (CaM) and Ca 2+ (Ben‐Johny et al ., ), was suggested to operate in higher plants (Köhler et al ., ; Köhler & Neuhaus, ). Binding CaM in the presence of elevated [Ca 2+ ] cyt.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 99%
“…Ben-Johny et al [11]). Quantification of current kinetics and steady state activation of CaV1.2 by Beyl et al [16] revealed the following sequence of events: At rest, the voltage sensors (VSs) are pulled into a down position by the electrical field.…”
Section: Introductionmentioning
confidence: 99%